A Low Cost HPIB Compatible Interface to a Thermochuck for Computerised C-V Measurement System - C.K Kwok; C.H Ling; R Kanhere; L.K AH (ASEAN Journal on Science and Technology for Development, 1988)
A Low Cost HPIB Compatible Interface to a Thermochuck for Computerised C-V Measurement System